Leptospirosis outcomes in pregnancy - parvaneh rezasoltani; fatemeh rafat (Journal of Holistic Nursing and Midwifery)
Introduction: Leptospirosis is a serious disease of humans, caused by different strains of the ‎bacteria Leptospira. The disease in humans can include pregnant mothers with poor outcomes ‎such as intrauterine fetal death, abortion, and delivery of a newborn with signs of congenital ‎leptospirosis. Moreover, due to overlapping signs and symptoms, leptospirosis is often ‎difficult to distinguish from HELLP syndrome and Acute Fatty Liver of pregnancy. ‎Therefore, it's necessary to assess the effect of leptospirosis on pregnancy outcome in human.‎